Ritual Values of Bengali Culture: Exploring Bengali Culture, History, and Contemporary Issues through Ritual Values (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There are abundant references in the novel to Bengali culture and history, extending from the painter Jainul Abedin to the pre-frontier territory of Bengali weaving industry to the syncretic religious customs of Bengal through Chanu's appearance, and there are additionally vignettes from the genuine setting back home through Hasina's letters. Ali additionally contacts upon variables basic the radicalization of Bengali Muslim youth, for example the neo-colonialist foul play in the Muslim world at present and furthermore the British colonialist nearness and orderly treacheries in the Indian subcontinent previously, yet her narrativisation is problematized by the way that these are voiced by Karim and Chanu separately - two people who can't be paid attention to. Their sarcastic treatment in the book renders them problematic as reference focuses.